2014 8th. Malaysian Software Engineering Conference (MySEC) 2014
DOI: 10.1109/mysec.2014.6986003
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of aspect design notations with respect to reusability and maintainability of models

Abstract: Aspect-oriented design notations improve the reusability and maintainability of models by means of separating crosscutting concerns from the core functionality of the system. However, as different design notations propose dissimilar ways of modeling and composing the crosscutting and core concerns, the capabilities of aspect design notations with regards to producing highly reusable and maintainable models may also vary. In this paper, we apply a selected set of aspect modeling notations to a modeling scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…UML has been the de factomodeling language in AOM. For instance, authors of [13] evaluate several aspect modeling notations in order to evaluate them with respect to reusability and maintainability of the obtained models. They concluded that having Reusable Aspect Models performs well against the majority of the employed metrics.…”
Section: Related Workmentioning
confidence: 99%
“…UML has been the de factomodeling language in AOM. For instance, authors of [13] evaluate several aspect modeling notations in order to evaluate them with respect to reusability and maintainability of the obtained models. They concluded that having Reusable Aspect Models performs well against the majority of the employed metrics.…”
Section: Related Workmentioning
confidence: 99%